Imports and Exports at the Level of the Firm: Evidence from Belgium - Mirabelle Muûls; Mauro Pisu (National Bank of Belgium, 2007)
This paper explores a newly-available panel data set merging balance sheet and international trade transaction data for Belgium. Both imports and exports appear to be highly concentrated among few firms and seem to have become more so over time. Focusing on manufacturing, we find that facts previously reported in the literature for exports only actually apply to imports too. We note that the number of trading firms diminishes as the number of export destinations or import origins increases. The same is true if we consider the number of products traded. With regard to productivity differentials, firms that both import and export appear to be the most productive, followed, in descending order, by importers only, exporters only and non-traders. These results point to the presence of fixed costs not only of exporting, but also of importing and to a process of self-selection in both export and import markets. Also, the productivity advantage of exporters reported in the literature may be overstated because imports were not considered.
Keywords: F10; F16; J21; 330; imports; exports; productivity; firms; Import; Export; Produktivität; Internationale Wirtschaft; Schätzung; Belgien